2016
DOI: 10.1039/c6cc01479h
|View full text |Cite
|
Sign up to set email alerts
|

Flavin-sensitized electrode system for oxygen evolution using photo-electrocatalysis

Abstract: Fabrication of bio-electrode systems decorated with redox active biomolecules, flavins, is demonstrated. Exploiting the photochemistry and electrochemistry of flavins, we explored the photo-electrochemical activity of flavin-functionalized electrode systems to assess their potential utility for sustainable energy production. As model systems, lumiflavin and flavin adenine dinucleotide were immobilized on carbon electrodes by dropcasting and covalent grafting techniques. Activity of these bio-electrodes towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…However, flavin's utility has already been appreciated based on empirical efforts, and elegant studies have employed flavins immobilized on electrodes or carbon nanotubes 85 as well as in a mobile phase of batteries. 86 Moreover, the electronic transitions we calculated are also being exploited in cases where flavins are in use as sensitizers for photochemical cells 85,87,88 or sensors. 89 While proteins tune flavin reactivity via multiple noncovalent interactions, we have demonstrated that even modification at a single position can change the way electron density is redistributed within the molecule as well as the associated energies.…”
Section: Concluding Remarks and Implications For Applicationsmentioning
confidence: 99%
“…However, flavin's utility has already been appreciated based on empirical efforts, and elegant studies have employed flavins immobilized on electrodes or carbon nanotubes 85 as well as in a mobile phase of batteries. 86 Moreover, the electronic transitions we calculated are also being exploited in cases where flavins are in use as sensitizers for photochemical cells 85,87,88 or sensors. 89 While proteins tune flavin reactivity via multiple noncovalent interactions, we have demonstrated that even modification at a single position can change the way electron density is redistributed within the molecule as well as the associated energies.…”
Section: Concluding Remarks and Implications For Applicationsmentioning
confidence: 99%
“…Reduction potentials were determined by cyclic voltammetry of 1 mM solutions of PAB, AB, and BA using a glassy carbon working electrode, platinum wire counter electrode, and Ag/AgCl reference electrode (catalog nos. CH104, CHI115, and CHI111 from CH Instruments Inc., Austin, TX) in 5 ml of 500 mM potassium phosphate, 100 mM KCl, pH 7.0 (47). Saturated quinhydrone in the same buffer was also analyzed to calibrate the system at 84 Ϯ 10 mV and 22°C (48).…”
Section: Reduction Potentials Of Exogenous Donorsmentioning
confidence: 99%
“…This plot shows three anodic (A′, B′, and C′) and three cathodic (A, B, and C) peaks. These correspond to the oxygen evolution process (A-A′) [ 28 ], the ferricyanide/ferrocyanide redox couple (B–B′) [ 26 ], and the reduction of oxygenated species (C–C′) [ 29 ] on the working electrode, as reported in the literature. The reversibility of these reactions relates to their voltammogram features: peaks A-A′ represent an irreversible reduction reaction, peaks B–B′ show a quasi-reversible reaction, and the C–C′ peaks, an irreversible oxidation reaction.…”
Section: Resultsmentioning
confidence: 95%